2016
DOI: 10.18869/acadpub.jnms.3.2.32
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' management of fever of children in Sabzevar

Abstract: Background and Purpose: Fever is one of the most frequent disease symptoms and a common cause of emergency admissions in infants and children. Considering the alarming nature of fever and pivotal role of mothers in the management of this symptom in children, this study aimed to evaluate the ability of fever management among mothers in Sabzevar city, Iran. Materials and Methods:This cross-sectional study was conducted on 340 mothers with children aged less than 10 years referring to the healthcare centers of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…In reviewing more recent studies, parents found to have better level of knowledge regarding fever, and most parents described normal and febrile temperature. [ 14 16 18 ] The reason for this, possibly, is due to increasing health education activities of public, especially parents for their kids health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In reviewing more recent studies, parents found to have better level of knowledge regarding fever, and most parents described normal and febrile temperature. [ 14 16 18 ] The reason for this, possibly, is due to increasing health education activities of public, especially parents for their kids health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a newly published study by Talebi et al .,[ 16 ] 67.4% of the mothers reported measuring the body temperature by touching the hand of the child, while 24.8% of the them used a thermometer. In a more recent published article in Turkey by Yavuz et al .,[ 20 ] 45.8% of parents measure fever with a thermometer prior and only 38% of them used the thermometer correctly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ROS may also lead to mutations such as point mutations and polymorphism and thus reduce semen quality. This study agree with Yoshida M, et al, 2012[16], who studied the effect of NPs reduction is related to lyedig cell degeneration and the damage to the seminiferous tubules.As Talebiet AR, et al 2013, [17] reported, regarding epididymis sperm characteristics including mobility, the percentage of normal cells compared to abnormal ones.…”
Section: Discussionmentioning
confidence: 96%